(untitled) (TAJ: Journal of Teachers Association, 2009)
This study was carried out with an aim to investigate the relationship between gastric metaplasia with H. pylori and the effect of eradication therapy. A total of 210 patients with history of dyspepsia were included in the study of which 50 were enrolled in the eradication therapy. After the eradication therapy 35 patients came for follow-up endoscopy. Paired endoscopic biopsies were taken from antrum and duodenal ulcer margin and were examined for H. pylori and for duodenitis and gastric metaplasia. Gastric metaplasia was significantly associated with H. pylori. After eradication H. pylori showed further extension of gastric metaplasia. It can be recommended that these patients can be further followed up to see the course of gastric metaplasia and what impact it has on ulcer recurrence and re-infection. doi: 10.3329/taj.v15i2.3908 TAJ December 2002; Vol.15(2):59-63